1987
DOI: 10.1002/cbf.290050206
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by elastase inhibitors of the formyl met leu phe‐induced chemotaxis of rat polymorphonuclear leukocytes

Abstract: Rat leukocyte elastase has been purified successively by AH-Sepharose Kappa-elastin affinity chromatography and by ion exchange chromatography on a carboxymethyl Sephadex resin. It has great similarities with human leukocyte elastase in its molecular weight, substrate specificity and inhibitory profile. The effect of rat leukocyte elastase inhibitors in influencing the chemotactic response of rat PMN to fMetLeuPhe has been compared to that of other proteinase inhibitors. The results indicated that oleoyl (Ala)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Polarization is generally considered as a consequence of reorganization of microfilaments or disassembly of microtubles, both cytoskeletons which are effectors of locomotic and contractile responses of PMNS (Kelley et al 1984). Events subsequent to the bindig of fMLP to its receptor remain to be determined, although cell surface chymotrypsin-like proteinase, which can be inactivated by the inhibitors employed in the present study, has been implicated in transducing an intracellular cue for microfilament reorganization (Hornbeck et al 1987). On the other hand, the finding that the addition of proteinase inhibitors had no effect on colchicineinduced polarization supports direct disassembly of microtubles by colchicine without activation of the cell surface enzyme as previously indicated (Kelley et al 1984).…”
Section: Discussionmentioning
confidence: 89%
“…Polarization is generally considered as a consequence of reorganization of microfilaments or disassembly of microtubles, both cytoskeletons which are effectors of locomotic and contractile responses of PMNS (Kelley et al 1984). Events subsequent to the bindig of fMLP to its receptor remain to be determined, although cell surface chymotrypsin-like proteinase, which can be inactivated by the inhibitors employed in the present study, has been implicated in transducing an intracellular cue for microfilament reorganization (Hornbeck et al 1987). On the other hand, the finding that the addition of proteinase inhibitors had no effect on colchicineinduced polarization supports direct disassembly of microtubles by colchicine without activation of the cell surface enzyme as previously indicated (Kelley et al 1984).…”
Section: Discussionmentioning
confidence: 89%
“…They showed that the inhibition of this enzyme by organophosphorus compounds reduced neutrophil chemotaxis (8,9) but were unsure as to the identity of the natural substrate or inhibitor (10). Other workers have reported that chloromethylketone inhibitors of chymotrypsin-like proteinases were able to suppress human neutrophil chemotaxis (11)(12)(13) and superoxide production (14) as well as attenuating membrane potential changes in rat neutrophils (15). Furthermore King and co-workers (16) reported that a monoclonal antibody against human neutrophils inhibited superoxide anion generation in response to the chemotactic peptide fMLP 1 by binding to a surface chymotrypsin-like enzyme.…”
mentioning
confidence: 99%
“…Laminin is involved in the interaction between epithelial cells and basement membrane components, such as collagen type IV (5,6). Elastin was originally considered to be an isotropic and inert constituent, but physicochemical studies have pointed to a more dynamic structure and to possible interactions with other connective tissue proteins (7,8). Elastin peptides were also shown to be able to interact with several other cell types (9, 10).…”
mentioning
confidence: 99%